TEACHING ENGLISH THROUGH ZOOM VIDEO CONFERENCING: SOME EFL TEACHERS’ EXPERIENCES - Dian Indrianis Fitri; Rifqi Hadiyatulloh; Muhammad Arif Sanjaya (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
This article attempts to explore the EFL teachers’ experiences in using zoom video conferencing platform as the technological massive changes during remote learning in the pandemic situation. The research question is how EFL teachers’ experience in the perception toward zoom video conferencing platform. The aims are to know EFL teachers’ experience toward zoom video conferencing platform in the perception of its usefulness, ease of use and satisfaction during the zoom video session. The design of this study is a mixed method analysis. The data instrument was collected using close ended questionnaire and interview. The data was gathered from 27 respondents. The findings are most of teachers have positive experience on its usefulness, attractiveness and user friendly. Only few teachers have negative experiences due to the limited internet quota and unstable connection.